Risk Factors for Progression in Vestibular Schwannomas After Incomplete Resection: A Single Center Retrospective Study - Li, Jiuhong; Deng, Xueyun; Ke, Daibo; Cheng, Jian; Zhang, Si; Hui, Xuhui (Frontiers in Neurology, 2021)
Background and Purpose: The risk factors for progression in vestibular schwannomas (VSs) after incomplete resection (IR) remain to be elucidated. The purpose of this study was to investigate the risk factors for progression in remnant VSs after surgery. Methods: From January 2009 to January 2018, 140 consecutive patients who underwent IR of VSs via suboccipital retrosigmoid approach in our institution were retrospectively analyzed. During follow-up, if progression was detected, the patient was classified into Progressive Group (PG); if the residual tumor was stable or shrank, the patient was classified into Stable Group (SG). Univariate analysis and multivariate analysis were used to evaluate the risk factors for progression after IR of VSs. Results: After a mean follow-up of 80.4 months (range, 24–134 months), 35 (25.0%) patients (PG) had a progression, and no progression was detected in 105 (75.0%) patients (SG). The average tumor size was 36.5 ± 8.9 mm in PG and 31.0 ± 9.8 mm in SG, respectively. The residual tumor volume was 304.6 ± 443.3 mm3 in PG and 75.9 ± 60.0 mm3 in SG, respectively. Univariate analysis showed that preoperative tumor size, residual tumor volume, and irregular internal auditory canal (IAC) expansion were significantly different between the two groups, whereas gender, age, cystic component, or Ki-67 labeling index (LI) did not differ significantly between the two groups. Multivariate analysis showed residual tumor volume was the independent risk factor for progression. Conclusions: VSs that underwent IR with larger preoperative size, greater residual tumor volume, or irregular IAC expansion may have a higher progression rate. Strict follow-up with shorter interval in these patients to detect early progression is necessary.